2021
DOI: 10.1186/s12993-021-00176-y
|View full text |Cite
|
Sign up to set email alerts
|

Linalool odor‐induced analgesia is triggered by TRPA1-independent pathway in mice

Abstract: We had recently reported that linalool odor exposure induced significant analgesic effects in mice and that the effects were disappeared in olfactory-deprived mice in which the olfactory epithelium was damaged, thus indicating that the effects were triggered by chemical senses evoked by linalool odor exposure. However, the peripheral neuronal mechanisms, including linalool receptors that contribute toward triggering the linalool odor-induced analgesia, still remain unexplored. In vitro studies have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Among these aldehydes, ketones, and alcohol components, benzyl alcohol is mostly as fragrance ingredients and preservatives in cosmetic products (Johnson et al, 2017). It was reported that linalool odor-induced analgesia was triggered through a TRPA1-independent pathway in mice (Kashiwadani et al, 2021). Decanal could protect human dermal fibroblasts against UVB-induced photoaging via the cAMP pathway (Kang et al, 2020), and the 2-hexenal inhibit Aspergillus flavus spore germination involving disruption of mitochondrial energy metabolism and induction of early apoptosis (Ma et al, 2019).…”
Section: Volatile Constituentsmentioning
confidence: 99%
“…Among these aldehydes, ketones, and alcohol components, benzyl alcohol is mostly as fragrance ingredients and preservatives in cosmetic products (Johnson et al, 2017). It was reported that linalool odor-induced analgesia was triggered through a TRPA1-independent pathway in mice (Kashiwadani et al, 2021). Decanal could protect human dermal fibroblasts against UVB-induced photoaging via the cAMP pathway (Kang et al, 2020), and the 2-hexenal inhibit Aspergillus flavus spore germination involving disruption of mitochondrial energy metabolism and induction of early apoptosis (Ma et al, 2019).…”
Section: Volatile Constituentsmentioning
confidence: 99%
“…To understand their putative pain relief properties, we reduced this group to monoterpenes associated with antiinflammatory activity (de Cássia da Silveira e Sá et al, 2013) that is mediated at least through an anti-TNF-α activity (Chen et al, 2021;Hilfiger et al, 2021). We combined data reporting a modulation of the TRPV1, TRPA1, or TRPM8 activity to define a group of anti-inflammatory phytocompound modulators of TRP channels (Xu et al, 2005;de Sousa et al, 2010;Ortar et al, 2012;de Cássia da Silveira e Sá et al, 2013;Guimarães et al, 2013;Rufino et al, 2014;Takaishi et al, 2014;Mihara and Shibamoto, 2015;Ohtsubo et al, 2015;Dai, 2016;Kaimoto et al, 2016;Oz et al, 2017;Wang et al, 2017;Chamanara et al, 2019;de Christo Scherer et al, 2019;Quintans et al, 2019;Soleimani et al, 2019;Ghosh et al, 2020;Heblinski et al, 2020;Hilfiger et al, 2020;Islam et al, 2020;Zhu et al, 2020;Chen et al, 2021;Dos Santos et al, 2021;Kashiwadani et al, 2021) (Table 1). Both menthol and pulegone, among other monoterpenes, match these properties (Table 1).…”
Section: Pulegone and Menthol As Potent Analgesic And Anti-inflammato...mentioning
confidence: 99%
“…Considering its physiological function in the gastrointestinal tract, TRPA1 agonists, such as allicin and AITC, might exert a regulatory influence on gastrointestinal motility ( Tsuchiya and Kawamata, 2019 ). The stimulation of TRPA1 receptors in the intestine by dietary compounds such as AITC, cinnamaldehyde, and linalool ( Fothergill et al, 2016 ; Kashiwadani et al, 2021 ) triggers mucosal defense mechanisms ( Table 2 ). When food components activate TRPA1 on enterocytes, they enhance transmucosal ion currents, which in turn facilitate nutrient absorption ( Fothergill et al, 2016 ).…”
Section: Trpa1 In the Gastrointestinal Tractmentioning
confidence: 99%